Dennotation, Connotation, And Myth Meanings In Mariah Carey’s Song Lyrics Through The Rain - Chintia Handayani (Jurnal Ilmiah Multidisiplin, 2025)
Semiotics a field linked to linguistics, studies how signs convey meaning. Unlike traditional linguistics, semiotics also includes symbols, images, and context in its analysis. When it comes to analyzing song lyrics, both linguistic and semiotic methods are essential in revealing the deeper meanings hidden in artistic expression. Lyrics frequently make use of figurative language such as metaphors and symbols, making them ideal subjects for semiotic exploration. The aim of this research is to analyze denotation, connotation, and myth meanings in Mariah Carey’s song lyrics “Through the Rain” using theory from Roland Barthes. And this research used qualitative descriptive method for this research. In this research, the researcher found 19 signs of denotation, connotation, and myth in Mariah Carey’s song entitled “Through the Rain”. The song "Through the Rain" by Mariah Carey describes as a powerful message of resilience, hope, and inner strength in the face of adversity.